If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11(n + -6) = 100n Reorder the terms: 11(-6 + n) = 100n (-6 * 11 + n * 11) = 100n (-66 + 11n) = 100n Solving -66 + 11n = 100n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-100n' to each side of the equation. -66 + 11n + -100n = 100n + -100n Combine like terms: 11n + -100n = -89n -66 + -89n = 100n + -100n Combine like terms: 100n + -100n = 0 -66 + -89n = 0 Add '66' to each side of the equation. -66 + 66 + -89n = 0 + 66 Combine like terms: -66 + 66 = 0 0 + -89n = 0 + 66 -89n = 0 + 66 Combine like terms: 0 + 66 = 66 -89n = 66 Divide each side by '-89'. n = -0.7415730337 Simplifying n = -0.7415730337
| 29-8k+16k= | | -15=12-3x | | 1/7x-1/2x=-1/14 | | -5+2x=7 | | 5u-4=6 | | 4(m+4)=60 | | 8x+1+15x+10=360 | | 8x+1+15x+10=180 | | 2x(x+5)=25 | | 2(x+2)=144 | | y=x^7-6x^4-2x | | 9(x+8)=2(x+6) | | 30000+15x=40 | | (8a^-6)^-4/3 | | 0=8x^2-18x | | 4x^4-10x^3+31x^2+15x+9=0 | | 3x-27y=16 | | -7+4(7x+2)=-8 | | 2x-3+3= | | a+450b=126000 | | 2b+8=20 | | 2*-3+3= | | 57=-3r | | 4t+3=t | | R-16=-9 | | 889-615=5 | | 3XY^2+5X^2Y-7XY^2+14X^2Y= | | R/6-2=5 | | =9x-7i+3(3x-7u) | | 4v-8+3v=20 | | 8n-3=5 | | 7sinx+2=4sinx |